Kinetics of optical phonons and DP depolarization of spins in drift transport: Hot carrier spin effect in semiconductors - M. Idrish Miah (Department of Physics, Sebelas Maret University, 2024)
Spin-conserving transport of carriers is an essential requirement for the practical semiconductor-based spintronic devices. Kinetics of optical phonons and Dyakonov-Perel (DP) depolarization of spins in drift transport in semiconductor gallium arsenide (GaAs) is theoretically investigated. We consider electrons in n-type bulk GaAs subjected to a strong electric field, where the electron distribution is assumed to be drifted Maxwellian. The momentum drift of this distribution results in the enhanced drift velocity, and electrons with the corresponding energy emit optical hot phonons in the drifting process. The hot phonons are incorporated via the longitudinal polar optical phonon (POP) mechanism in the momentum relaxation. It is found that a finite phonon lifetime can reduce the momentum relaxation rate, which results in a delay in the runaway to higher fields, where the effect increases with the electron density. The electron spin is found to relax with the DP relaxation frequencies, and the DP spin lifetimes are found to decrease with increasing the drift field. However, a high field completely depolarizes the electron spin due to an increase of the DP spin precession frequency of the hot electrons in the POP scattering process. It is also found that the DP spin precession frequency decreases with decreasing electron temperature or increasing electron density in the moderate range. However, the findings resulting from this investigation demonstrate the hot carrier effect in the spin transport in semiconductors. The results are discussed in comparison with those obtained in earlier experimental and theoretical studies with different approaches.